2022
DOI: 10.3390/membranes12060578
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals That ADAM15 Can Have Proteolytic-Independent Functions in the Steady State

Abstract: A disintegrin and metalloproteinase 15 (ADAM15) is a member of the ADAM family of sheddases. Its genetic ablation in mice suggests that ADAM15 plays an important role in a wide variety of biological functions, including cartilage homeostasis. Nevertheless, while the substrate repertoire of other members of the ADAM family, including ADAM10 and ADAM17, is largely established, little is known about the substrates of ADAM15 and how it exerts its biological functions. Herein, we used unbiased proteomics to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Thus, we treated SW 1353 chondrosarcoma cells with DMOG, a compound that stabilizes HIF-1α, thereby mimicking hypoxia [ 14 , 50 , 51 ], and performed a quantitative secretome analysis to identify proteins that were differentially released in response to hypoxia. SW 1353 cells represent a model that we have extensively investigated and the secretome of which we have fully characterized [ 52 , 53 ]. We found that approximately 50% of the total proteins were altered in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we treated SW 1353 chondrosarcoma cells with DMOG, a compound that stabilizes HIF-1α, thereby mimicking hypoxia [ 14 , 50 , 51 ], and performed a quantitative secretome analysis to identify proteins that were differentially released in response to hypoxia. SW 1353 cells represent a model that we have extensively investigated and the secretome of which we have fully characterized [ 52 , 53 ]. We found that approximately 50% of the total proteins were altered in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ADAM15 catalytic activity was required for claudin-1-dependent regulation of growth and mobility of breast cancer cells ( Mattern et al, 2019 ), but was not required for its role in promoting pathological neovascularization in a mouse model of oxygen-induced retinopathy ( Maretzky et al, 2014 ). Similarly, we found that ADAM15 regulates levels of TIMP-3 in a catalytic-independent manner ( Yang et al, 2022 ). For this reason, we here used a cutting-edge proteomic method that is specifically designed to enrich cell membrane proteins, and therefore could allow identification both of canonical ADAM15 substrates and proteins regulated by the proteinase through other catalytic-independent mechanisms.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, we further investigated ADAM15-dependent shedding by using data-independent acquisition mass spectrometry (DIA-MS). DIA-MS is a recently-developed global MS-based strategy that allows a broader protein coverage than data-dependent acquisition (DDA) MS, which was previously used to investigate changes in the secretome of ADAM15-silenced cells ( Yang et al, 2020 ; Yang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations